Amaranthus gangeticus (Amaranthaceae), a name incertae sedis - Iamonico, Duilio (Phytotaxa, 2014)
As part of the revision of the genus Amaranthus Linnaeus (1753: 989) for the treatment of Amaranthaceae Jussieu for the Euro+Med PlantBase project (Iamonico, in prep.), and the typification work on the Linnaean names in this family (e.g., Iamonico 2012, 2013, 2014a, 2014b, Iamonico & Jarvis 2012, Iamonico & Del Pino 2014), it has been necessary to establish the identity of A. gangeticus Linnaeus (1759: 1268), especially in comparison with the related taxa included in the A. tricolor Linnaeus (1753: 989) aggregate (Iamonico 2014a).